Conceptual model of patho- and sanogenesis of the sacroiliac joint osteoarthritis - Korzh, Mykola; Staude, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective. To develop a conceptual model of patho- and sanogenesis of the sacroiliac joint (SIJ) osteoarthritis on base of the known data about the SIJ, the results of our own biomechanical studies of this joint, its ligaments and stabilizing muscles by finite element modelling, data of clinical verification of these results. Methods. The object of the model is the SIJ as a link, which connects the spine and pelvis. The proposed conceptual model is based on the M. Panjabi hypothesis of chronic lumbar pain in the case of partial damage to ligaments, which leads to muscle dysfunction. Results. A new conceptual model of SIJ osteoarthritis was developed. In this model we tried to take into account the limitations of the existing SIJ stability hypotheses and models of the appearance of the pelvic girdle pain, SIJ dysfunction and SIJ arthrosis. The model is based on the results of our own research. It was proved, that patients with SIJ osteoarthritis have an asymmetry of the width of the joint slits, the inclination of the sacrum and pelvis, sacral rotation, hyperlordosis in the LV–SI segment. These factors lead to a shift of the horizontal axis of sacral rotational mobility relative to the pelvic bones. This horizontal axis shift leads to the instability of the SIJ on one side of the joint, and to the functional block on another side. The results of these functional changes were damage of the SIJ ligaments-stabilizers, dysfunction of the SIJ muscles-stabilizers, degenerative changes of SIJ elements and pain. The developed model allows to explain the distortion of muscular response pattern in patients with improper SIJ biomechanics in conditions of SIJ osteoarthritis. The increase of the SIJ biomechanics changes enlarges the the muscle response pattern distortion. Conclusions. The developed conceptual model explains many clinical manifestations of the SIJ osteoarthritis and will help to understand better the mechanics of the pelvic girdle pain in such conditions, will improve the results of diagnosis and treatment.